Wear-resistant coating, preparation method and application of wear-resistant coating to alumite color layer

By using modified silicon carbide/silica composite materials and multifunctional modifiers, the wear resistance and antibacterial properties of electroplated aluminum color coatings were solved, and the overall performance of the coatings was improved.

CN121293870APending Publication Date: 2026-01-09SHANTOU JIAXIN PACKING MATERIAL CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202511784217.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-01
Publication Date
2026-01-09

AI Technical Summary

Technical Problem

Existing technologies cannot simultaneously achieve both the wear resistance and antibacterial properties of electroplated aluminum color coatings.

Method used

By preparing surface-modified silicon carbide/silica composite materials and grafting silane coupling agent KH-560 onto them, combined with an antibacterial quaternary ammonium salt structure, an organic-inorganic hybrid filler was prepared. Multifunctional modifiers and crosslinking agents pentaerythritol tetrakis(3-mercaptopropionic acid) were added to improve the mechanical, wear-resistant and antibacterial properties of polyurethane acrylate coatings.

Benefits of technology

It improves the mechanical properties, wear resistance, and antibacterial properties of the coating, enhances the adhesion between the coating and the aluminum plating layer, and forms a dense coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121293870A_ABST
    Figure CN121293870A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high-performance coatings, and discloses a wear-resistant coating, a preparation method and application of the wear-resistant coating to an alumite color layer. The preparation method of the wear-resistant coating comprises the following steps: reacting 1, 6-dibromohexane with p-hydroxybenzaldehyde to obtain an intermediate product A; reacting the intermediate product A with p-phenylenediamine to obtain an intermediate product B; modifying the surface modified silicon carbide / silicon dioxide composite material with the intermediate product B to obtain an organic-inorganic hybrid filler; treating the organic-inorganic hybrid filler with N-methyldiethanolamine to obtain a modified organic-inorganic hybrid filler; the preparation method comprises the following steps: preparing a waterborne polyurethane acrylate emulsion by taking a multifunctional modifier, a modified organic-inorganic hybrid filler and tetrakis (3-mercaptopropionic acid) pentaerythritol ester as raw materials; and mixing the waterborne polyurethane acrylate emulsion with other auxiliaries to obtain the wear-resistant coating. The wear-resistant coating provided by the invention has good mechanical properties, wear resistance, heat resistance and antibacterial properties, and can be used in an alumite color layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of high-performance coatings technology, specifically to a wear-resistant coating, its preparation method, and its application on anodized aluminum color layers. Background Technology

[0002] Electroplated aluminum hot stamping foil (commonly known as electroplated aluminum) is used in a wide range of applications, including anti-counterfeiting and labeling of product packaging, surface finishing of plastic products, surface decoration of building materials and furniture, transfer printing of fabrics, trademarks and book covers, as well as on craft and cultural products, banknotes, visas, credit cards, and other important documents. Electroplated aluminum hot stamping foil is made by coating a release layer, a coloring layer, an aluminum plating layer, and an adhesive layer sequentially onto its surface, followed by gradient high-temperature drying. The color coating of electroplated aluminum can be made with or without color powder, depending on the product requirements, resulting in different colors. Good color coatings should have high transparency and heat resistance. Furthermore, electroplated aluminum hot stamping foil is frequently used and easily worn in daily necessities, and it comes into frequent contact with the human body. If the coating lacks antibacterial properties, it may lead to the growth of microorganisms, posing a safety hazard to users.

[0003] To address the above issues, Chinese patent application CN107629603A discloses a wear-resistant color coating and the resulting wear-resistant color layer, wear-resistant electroplated aluminum, and its preparation method. Chinese patent application CN119955362A proposes an antibacterial UV-curable electroplated aluminum color coating and its preparation method. However, neither of these patent applications can simultaneously achieve both the wear resistance and antibacterial properties of the color coating. Summary of the Invention

[0004] To address the aforementioned technical problems, this invention provides a method for preparing a wear-resistant coating, comprising the following steps: Step 1: 1,6-Dibromohexane reacts with p-hydroxybenzaldehyde to give intermediate A; intermediate A reacts with p-phenylenediamine to give intermediate B. Step 2: Modify the surface-modified silicon carbide / silica composite material with intermediate product B to obtain an organic-inorganic hybrid filler; treat the organic-inorganic hybrid filler with N-methyldiethanolamine to obtain a modified organic-inorganic hybrid filler. Step 3: Introduce the multifunctional modifier, modified organic-inorganic hybrid filler, and pentaerythritol tetrakis(3-mercaptopropionic acid) into the polyurethane acrylate structure to prepare an aqueous polyurethane acrylate emulsion; mix the aqueous polyurethane acrylate emulsion, diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, ethoxylated trimethylolpropane triacrylate, and titanium dioxide in a certain proportion to obtain a wear-resistant coating.

[0005] Preferably, in step one, the preparation method of intermediate product B specifically includes: adding 1,6-dibromohexane and potassium carbonate to acetonitrile, then adding 15wt% p-hydroxybenzaldehyde / acetonitrile mixture, heating to 67-73℃, refluxing for 5-7 hours, purifying to obtain intermediate product A; wherein the mass ratio of 1,6-dibromohexane, potassium carbonate, acetonitrile, and p-hydroxybenzaldehyde / acetonitrile mixture is (4.9-9.8):(2.8-5.6):(100-150):(16-32); adding p-phenylenediamine to acetonitrile... Then, intermediate product A is added, and the reaction mixture is reacted at 65-75℃ for 10-14 h, purified, and intermediate product B is obtained; wherein, the mass ratio of p-phenylenediamine, acetonitrile, and intermediate product A is (5.4-10.8):(250-350):(14.3-28.5); in the above process, the hydroxyl group of p-hydroxybenzaldehyde reacts with the bromine at the end of 1,6-dibromohexane to obtain intermediate product A; the aldehyde group in intermediate product A undergoes a Schiff base reaction with the amino group at the end of p-phenylenediamine to form a dynamic covalent bond with antibacterial effect—a Schiff base bond.

[0006] Preferably, in step two, the preparation method of the modified organic-inorganic hybrid filler specifically includes: adding the surface-modified silicon carbide / silica composite material to N,N-dimethylformamide, sonicating, then adding intermediate product B, reacting at 75-85℃ for 20-30h, purifying, and obtaining the organic-inorganic hybrid filler; wherein, the mass ratio of the surface-modified silicon carbide / silica composite material, N,N-dimethylformamide, and intermediate product B is (4-5):(100-150):(1.9-3.8); mixing the organic-inorganic hybrid filler, N,N-dimethylformamide, and N-methyldiethanolamine at a mass ratio of (4-5):(100-150):(2.2-3.6), stirring and reacting at 58-62℃ for 5-7h, purifying, and obtaining the modified organic-inorganic hybrid filler.

[0007] Further, the surface-modified silicon carbide / silica composite material is prepared by the following method: In an air atmosphere, silicon carbide is heated from room temperature to 1000-1200°C at a rate of 5°C / min, held for 1.5-2.5 hours, and then cooled to room temperature to obtain the silicon carbide / silica composite material; distilled water is mixed with silane coupling agent KH-560, stirred, and then ethanol and the silicon carbide / silica composite material are added. The pH of the mixture is adjusted to 4-5 with acetic acid, heated to 68-72°C, stirred for 5-7 hours, purified, and ground to obtain the surface-modified silicon carbide / silica composite material. Silica composite material; wherein, the mass ratio of distilled water, silane coupling agent KH-560, ethanol, and silicon carbide / silica composite material is (15-30):(5-10):(135-270):(4-5); In the above process, silicon carbide, as a high-hardness filler, can significantly enhance the wear resistance of the polymer. However, the high surface energy of silicon carbide particles leads to their easy agglomeration, and the chemical inertness of the silicon carbide surface results in poor compatibility with the polymer matrix. This invention forms a silicon oxide layer on the surface of silicon carbide through thermal oxidation, while generating abundant surface hydroxyl groups, and then grafts silane coupling agent KH-560 onto the silicon carbide. The binder KH-560 is used to achieve surface functionalization of modified silicon carbide / silica composites by introducing epoxy groups onto the surface of the modified silicon carbide / silica composites. The epoxy groups on the surface-modified silicon carbide / silica composites undergo ring-opening reactions with the amino groups in intermediate product B. Intermediate product B is then grafted onto the surface-modified silicon carbide / silica composites to obtain an organic-inorganic hybrid filler. Next, N-methyldiethanolamine is combined with the organic-inorganic hybrid filler through a quaternization reaction, introducing an antibacterial quaternary ammonium salt structure and hydroxyl groups onto the silicon carbide / silica composites. These hydroxyl groups can react with polyurethane... The reaction of isocyanate groups in acrylic polymers allows modified organic-inorganic hybrid fillers to be uniformly dispersed in the polyurethane acrylate matrix. Therefore, modified organic-inorganic hybrid fillers can serve as antibacterial nanofillers in waterborne polyurethane acrylate emulsions, improving the mechanical properties, wear resistance, heat resistance, and antibacterial properties of the waterborne polyurethane acrylate emulsion system. Furthermore, modified organic-inorganic hybrid fillers can form an organic-inorganic interpenetrating network with the polyurethane acrylate system, making the coating denser and further improving the mechanical properties, heat resistance, and wear resistance of the polyurethane acrylate coating material.

[0008] Preferably, in step three, the preparation method of the waterborne polyurethane acrylate emulsion specifically includes: adding polytetrahydrofuran and 2,2-dimethylolpropionic acid to N,N-dimethylacetamide, stirring, then adding a multifunctional modifier, stirring, then adding toluene diisocyanate and dibutyltin dilaurate, heating to 68-72°C, reacting for 2-3 hours, then adding trimethylolpropane, reacting at 68-72°C for 1.5-2.5 hours, and then adding pentaerythritol triacrylate... Hydroxyethyl methacrylate was reacted at 62-68℃ for 1.5-2.5 h, then modified organic-inorganic hybrid filler was added and reacted at 62-68℃ for 1-2 h, followed by the addition of triethylamine and the reaction at 62-68℃ for 10-15 min. The mixture was then rotary evaporated, deionized water was added to the reaction mixture, and the mixture was emulsified at 23-27℃ for 1 h. Finally, pentaerythritol tetrakis(3-mercaptopropionic acid) was added and reacted at 23-27℃ for 1-2 h to obtain an aqueous polyurethane acrylate emulsion.

[0009] In the above process, this invention introduces a multifunctional modifier and a modified organic-inorganic hybrid filler into a polyurethane acrylate system, resulting in a light-cured, transparent, waterborne polyurethane acrylate emulsion with excellent mechanical properties, wear resistance, heat resistance, and antibacterial properties. The multifunctional modifier of this invention contains an aromatic benzene ring structure, phosphate groups, dynamic acylhydrazone bonds, and phenolic hydroxyl groups. The aromatic benzene ring structure improves the mechanical properties and thermal stability of the polyurethane acrylate system, the phosphate groups have a positive impact on the heat resistance of the polyurethane acrylate system, and the phosphate groups can also have electrochemical properties. A strong adhesion is formed between aluminum atoms, and dynamic acylhydrazone bonds form a dynamic hydrogen bond network in the polyurethane acrylate system, increasing the crosslinking density of the system and thus improving the mechanical properties, wear resistance, and thermal stability of the polyurethane acrylate system. The presence of phenolic hydroxyl groups can synergistically interact with phosphate ester groups to form a strong interaction between the polyurethane acrylate coating and the aluminum plating layer. In addition, the present invention introduces pentaerythritol tetrakis(3-mercaptopropionic acid) as a crosslinking agent into the polyurethane acrylate system, further improving the mechanical properties, wear resistance, and heat resistance of the polyurethane acrylate system.

[0010] Further, the mass ratio of the multifunctional modifier, N,N-dimethylacetamide, polytetrahydrofuran, 2,2-dimethylolpropionic acid, toluene diisocyanate, dibutyltin dilaurate, trimethylolpropane, pentaerythritol triacrylate, hydroxyethyl methacrylate, modified organic-inorganic hybrid filler, triethylamine, deionized water, and pentaerythritol tetrakis(3-mercaptopropionic acid) ester is (13.3-26.6): (100-150): (20-40): (6.7-13.4): (20.8-41.5): (0.1-0.2): (13.2-16.6): (3.8-7.5): (1.7-3.3): (4.3-9.5): (5.1-10.1): (180-350): (6-15).

[0011] Preferably, in step three, the mass ratio of waterborne polyurethane acrylate emulsion, diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, ethoxylated trimethylolpropane triacrylate, and titanium dioxide in the wear-resistant coating is (80-100):(0.8-1.2):(8-10):(1.5-4.5); further, the multifunctional modifier in step three is prepared by the following method: Step S1: Mix hydroxyethyl methacrylate and hydroquinone monomethyl ether, stir at 0°C, then add phosphorus pentoxide, heat to 48-52°C, react for 5.5-6.5 h, then add hydroxyethyl methacrylate again, heat to 68-72°C, react for 40-80 min, purify to obtain the phosphate ester compound; wherein the mass ratio of hydroxyethyl methacrylate, hydroquinone monomethyl ether, and phosphorus pentoxide is (13.7-27.4):(1.5-3):( 7.1-14.2); 3-mercaptopropionic acid is added to ethanol and heated to 60-70℃. Then, a phosphate ester compound and a 0.5wt% azobisisobutyronitrile / ethanol mixture are added. The mixture is stirred and reacted for 3-5 hours. After purification, the modified phosphate ester compound is obtained. The mass ratio of 3-mercaptopropionic acid, ethanol, phosphate ester compound, and azobisisobutyronitrile / ethanol mixture is (2.1-4.2):(120-150):(3.2-6.4):(15-20). Step S2: Mix 13.1wt% succinic acid dihydrazide aqueous solution and 20wt% 4-amino-2-hydroxybenzaldehyde / ethanol mixture at a mass ratio of (28.7-57.5):(35-70), stir and react at 65-75℃ for 2.5-3.5h, and purify to obtain the hydrazide compound; mix the modified phosphate ester compound, N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride, N-hydroxysuccinimide, N,N-dimethylformamide, and hydrazide compound at a mass ratio of (5.3-10.6):(4.8-9.6):(2.8-5.6):(200-300):(7.7-15.4), stir and react at 60-80℃ for 6-10h, and purify to obtain the multifunctional modifier.

[0012] In the above process, hydroxyethyl methacrylate reacts with phosphorus pentoxide, and hydroquinone monomethyl ether is added as an inhibitor during the reaction to obtain a phosphate ester compound; the phosphate ester compound combines with 3-mercaptopropionic acid through the reaction of carbon-carbon double bonds and thiol groups to obtain a modified phosphate ester compound; succinic dihydrazide reacts with 4-amino-2-hydroxybenzaldehyde in a Schiff base reaction to obtain an acyl hydrazide compound; the acyl hydrazide compound combines with the modified phosphate ester compound through an amidation reaction to obtain a multifunctional modifier.

[0013] The wear-resistant coating is prepared using the aforementioned method.

[0014] Application of the wear-resistant coating on the electroplated aluminum color layer.

[0015] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention uses silicon carbide as raw material to prepare a silicon carbide / silica composite material by thermal oxidation. Then, silane coupling agent KH-560 is grafted onto the surface of the modified silicon carbide / silica composite material to achieve surface functionalization, which solves the problems of easy agglomeration of silicon carbide particles and poor compatibility with polymer matrix. Then, intermediate product B is grafted onto the surface-modified silicon carbide / silica composite material, and then antibacterial quaternary ammonium salt structure and hydroxyl groups are introduced. The modified organic-inorganic hybrid filler can also form an organic-inorganic interpenetrating network with the polyurethane acrylate system, giving the waterborne polyurethane acrylate coating excellent mechanical properties, wear resistance, heat resistance and antibacterial properties. 2. This invention combines hydrazide compounds with modified phosphate compounds to prepare a multifunctional modifier, and then introduces the multifunctional modifier into the polyurethane acrylate system to increase the crosslinking density of the polyurethane acrylate system. The presence of aromatic benzene ring structure, phosphate groups, dynamic hydrazone bonds and phenolic hydroxyl groups in the multifunctional modifier, together with the modified organic-inorganic hybrid filler, improves the comprehensive performance of waterborne polyurethane acrylate coatings and improves the adhesion between the coating and the aluminum plating layer. 3. This invention introduces pentaerythritol tetrakis(3-mercaptopropionic acid) as a crosslinking agent into the polyurethane acrylate system, which further improves the mechanical properties, wear resistance and heat resistance of polyurethane acrylate coatings. Attached Figure Description

[0016] Figure 1 This is a comparison chart of the wear resistance test results of electroplated aluminum film samples prepared using the wear-resistant coatings of Examples 3-5 and Comparative Examples 1-4 of the present invention. Figure 2 This is a schematic diagram illustrating the synthesis of intermediate product A in this invention; Figure 3 This is a schematic diagram illustrating the synthesis of intermediate product B in this invention; Figure 4 This is a schematic diagram illustrating the synthesis of the acylhydrazine compound of the present invention; Figure 5 This is a schematic diagram illustrating the synthesis of the phosphate ester compound of the present invention; Figure 6 This is a schematic diagram illustrating the synthesis of the modified phosphate compound of the present invention. Detailed Implementation

[0017] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0018] Example 1 This embodiment discloses a method for preparing a surface-modified silicon carbide / silica composite material, comprising the following steps: uniformly coating silicon carbide in a quartz boat, transferring the quartz boat to a muffle furnace, and heating it in air at a rate of 5°C / min from room temperature to 1100°C, holding for 2 hours, and cooling to room temperature to obtain the silicon carbide / silica composite material; mixing 22.5g of distilled water with 7.5g of silane coupling agent KH-560, stirring for 15 minutes, then adding 202.5g of ethanol and 4.5g of silicon carbide / silica composite material, adjusting the pH of the mixture to 4.5 with acetic acid, heating to 70°C, stirring for 6 hours, centrifuging after the reaction, washing the precipitate four times with ethanol, vacuum drying at 50°C, and grinding to obtain the surface-modified silicon carbide / silica composite material.

[0019] Example 2 This embodiment discloses a method for preparing a multifunctional modifier, including the following steps: Step S1: Mix 19.5g of hydroxyethyl methacrylate and 2.3g of hydroquinone monomethyl ether, stir at 0℃, then add 107g of phosphorus pentoxide in six equal portions to the above mixture, heat to 50℃, react for 6h, then add 1.1g of hydroxyethyl methacrylate, heat to 70℃, react for 60min, wash the reaction mixture with deionized water, and dry to obtain the phosphate ester compound; add 3.2g of 3-mercaptopropionic acid to 135g of ethanol, sonicate for 30min, heat to 65℃, then add 4.8g of the phosphate ester compound and 17.5g of 0.5wt% azobisisobutyronitrile / ethanol mixture, stir and react for 4h, after the reaction is complete, filter, wash, and dry to obtain the modified phosphate ester compound; Step S2: 43.1g of 13.1wt% succinic dihydrazide aqueous solution was added to 52.5g of 20wt% 4-amino-2-hydroxybenzaldehyde / ethanol mixture, and the mixture was stirred at 70℃ for 3h. After the reaction was completed, the mixture was filtered, and the resulting solid product was washed successively with deionized water and ethanol, and then dried under vacuum at 50℃ to obtain the hydrazide compound. 7.9g of modified phosphate ester compound, 7.2g of N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride, and 4.2g of N-hydroxysuccinimide were added to 250g of N,N-dimethylformamide, and then 11.6g of the hydrazide compound was added. The mixture was stirred at 70℃ for 8h. After the reaction was completed, the solvent was evaporated, and the resulting solid was washed with ethanol and dried to obtain the multifunctional modifier.

[0020] Example 3 This embodiment discloses a method for preparing a wear-resistant coating, including the following steps: Step 1: Add 4.9g of 1,6-dibromohexane and 2.8g of potassium carbonate to 100g of acetonitrile, then add 16g of a 15wt% p-hydroxybenzaldehyde / acetonitrile mixture dropwise at a rate of 0.8mL / min. Heat to 67℃ and reflux for 7h. After the reaction is complete, evaporate the solvent and filter to obtain intermediate product A. Add 5.4g of p-phenylenediamine to 250g of acetonitrile, then add 14.3g of intermediate product A dropwise at a rate of 0.8mL / min. React the reaction mixture at 65℃ for 14h. After the reaction is complete, filter, wash the obtained solid product three times with acetonitrile, and dry under vacuum at 65°C to obtain intermediate product B. Step 2: Add 4g of surface-modified silicon carbide / silica composite material to 100g of N,N-dimethylformamide, sonicate for 20min, then add 1.9g of intermediate product B, react at 75℃ for 30h. After the reaction, centrifuge, wash the obtained solid product three times with N,N-dimethylformamide, and vacuum dry at 50℃ to obtain organic-inorganic hybrid filler; add 4g of organic-inorganic hybrid filler to 100g of N,N-dimethylformamide, then add 2.2g of N-methyldiethanolamine, stir and react at 58℃ for 7h. After the reaction, centrifuge, wash the obtained solid product three times with N,N-dimethylformamide, and vacuum dry at 50℃ to obtain modified organic-inorganic hybrid filler; Step 3: Add 20g of polytetrahydrofuran and 6.7g of 2,2-dimethylolpropionic acid to 100g of N,N-dimethylacetamide and stir for 30 minutes. Then add 13.3g of multifunctional modifier and stir. Next, add 20.8g of toluene diisocyanate and 0.1g of dibutyltin dilaurate, heat to 68℃, and react for 2 hours. Then add 13.2g of trimethylolpropane and react at 68℃ for 2.5 hours. Then add 3.8g of pentaerythritol triacrylate and 1.7g of hydroxyethyl methacrylate and react at 62℃ for 2.5 hours. Next, add 4.3g of modified organic-inorganic hybrid filler and react at 62℃ for 2 hours. Finally, add 5.1g of triethylamine. The mixture was reacted at 62℃ for 15 min, and N,N-dimethylacetamide was removed by rotary evaporation. 180 g of deionized water was added to the reaction mixture, and the mixture was emulsified at 23℃ for 1 h. Then, 6 g of pentaerythritol tetrakis(3-mercaptopropionic acid) was added, and the mixture was reacted at 23℃ for 2 h to obtain an aqueous polyurethane acrylate emulsion. By weight, 80 parts of the aqueous polyurethane acrylate emulsion, 0.8 parts of diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, 8 parts of ethoxylated trimethylolpropane triacrylate, and 1.5 parts of titanium dioxide were mixed evenly to obtain a wear-resistant coating.

[0021] Example 4 This embodiment discloses a method for preparing a wear-resistant coating, including the following steps: Step 1: Add 9.8g of 1,6-dibromohexane and 5.6g of potassium carbonate to 150g of acetonitrile, then add 32g of a 15wt% p-hydroxybenzaldehyde / acetonitrile mixture dropwise at a rate of 1.2mL / min. Heat to 73℃ and reflux for 5h. After the reaction is complete, evaporate the solvent and filter to obtain intermediate product A. Add 10.8g of p-phenylenediamine to 350g of acetonitrile, then add 28.5g of intermediate product A dropwise at a rate of 1.2mL / min. React the reaction mixture at 75℃ for 10h. After the reaction is complete, filter, wash the obtained solid product 5 times with acetonitrile, and dry under vacuum at 65°C to obtain intermediate product B. Step 2: Add 5g of surface-modified silicon carbide / silica composite material to 150g of N,N-dimethylformamide, sonicate for 40min, then add 3.8g of intermediate product B, react at 85℃ for 20h. After the reaction, centrifuge, wash the obtained solid product 5 times with N,N-dimethylformamide, and vacuum dry at 50℃ to obtain organic-inorganic hybrid filler; add 5g of organic-inorganic hybrid filler to 150g of N,N-dimethylformamide, then add 3.6g of N-methyldiethanolamine, stir and react at 62℃ for 5h. After the reaction, centrifuge, wash the obtained solid product 5 times with N,N-dimethylformamide, and vacuum dry at 50℃ to obtain modified organic-inorganic hybrid filler; Step 3: Add 40g of polytetrahydrofuran and 13.4g of 2,2-dimethylolpropionic acid to 150g of N,N-dimethylacetamide and stir for 40 minutes. Then add 26.6g of multifunctional modifier and stir. Next, add 41.5g of toluene diisocyanate and 0.2g of dibutyltin dilaurate, heat to 72℃, and react for 2 hours. Then add 16.6g of trimethylolpropane and react at 72℃ for 1.5 hours. Then add 7.5g of pentaerythritol triacrylate and 3.3g of hydroxyethyl methacrylate and react at 68℃ for 1.5 hours. Next, add 9.5g of modified organic-inorganic hybrid filler and react at 68℃ for 1 hour. Finally, add 10.1g of triethylamine. The reaction mixture was stirred at 68℃ for 10 min, and N,N-dimethylacetamide was removed by rotary evaporation. 350 g of deionized water was added to the reaction mixture, and the mixture was emulsified at 27℃ for 1 h. Then, 15 g of pentaerythritol tetrakis(3-mercaptopropionic acid) was added, and the mixture was stirred at 27℃ for 1 h to obtain an aqueous polyurethane acrylate emulsion. By weight, 100 parts of the aqueous polyurethane acrylate emulsion, 1.2 parts of diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, 10 parts of ethoxylated trimethylolpropane triacrylate, and 4.5 parts of titanium dioxide were mixed evenly to obtain a wear-resistant coating.

[0022] Example 5 This embodiment discloses a method for preparing a wear-resistant coating, including the following steps: Step 1: Add 7.4g of 1,6-dibromohexane and 4.2g of potassium carbonate to 125g of acetonitrile, then add 24g of a 15wt% p-hydroxybenzaldehyde / acetonitrile mixture dropwise at a rate of 1mL / min. Heat to 70℃ and reflux for 6h. After the reaction is complete, evaporate the solvent and filter to obtain intermediate product A. Add 8.1g of p-phenylenediamine to 300g of acetonitrile, then add 21.4g of intermediate product A dropwise at a rate of 1mL / min. React the reaction mixture at 70℃ for 12h. After the reaction is complete, filter, wash the obtained solid product four times with acetonitrile, and dry under vacuum at 65°C to obtain intermediate product B. Step 2: Add 4.5g of surface-modified silicon carbide / silica composite material to 125g of N,N-dimethylformamide, sonicate for 30min, then add 2.8g of intermediate product B, react at 80℃ for 25h. After the reaction, centrifuge, wash the obtained solid product 4 times with N,N-dimethylformamide, and vacuum dry at 50℃ to obtain organic-inorganic hybrid filler; add 4.5g of organic-inorganic hybrid filler to 125g of N,N-dimethylformamide, then add 2.9g of N-methyldiethanolamine, stir and react at 60℃ for 6h. After the reaction, centrifuge, wash the obtained solid product 4 times with N,N-dimethylformamide, and vacuum dry at 50℃ to obtain modified organic-inorganic hybrid filler; Step 3: Add 30g of polytetrahydrofuran and 10.1g of 2,2-dimethylolpropionic acid to 125g of N,N-dimethylacetamide, stir for 35 minutes, then add 19.9g of multifunctional modifier, stir, then add 31.2g of toluene diisocyanate and 0.2g of dibutyltin dilaurate, heat to 70℃, react for 2.5 hours, then add 14.9g of trimethylolpropane, react at 70℃ for 2 hours, then add 5.7g of pentaerythritol triacrylate and 2.5g of hydroxyethyl methacrylate, react at 65℃ for 2 hours, then add 6.9g of modified organic-inorganic hybrid filler, react at 65℃ for 1.5 hours, and finally add 7.6g of triethylamine. The reaction mixture was stirred at 65℃ for 12 min, and N,N-dimethylacetamide was removed by rotary evaporation. 265 g of deionized water was added to the reaction mixture, and the mixture was emulsified at 25℃ for 1 h. Then, 10.5 g of pentaerythritol tetrakis(3-mercaptopropionic acid) was added, and the mixture was stirred at 25℃ for 1.5 h to obtain an aqueous polyurethane acrylate emulsion. By weight, 90 parts of the aqueous polyurethane acrylate emulsion, 1 part of diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, 9 parts of ethoxylated trimethylolpropane triacrylate, and 3 parts of titanium dioxide were mixed evenly to obtain a wear-resistant coating.

[0023] The surface-modified silicon carbide / silica composite material and the multifunctional modifier in Examples 3-5 above are the surface-modified silicon carbide / silica composite material prepared in Example 1 and the multifunctional modifier prepared in Example 2.

[0024] Comparative Example 1 This comparative example discloses a method for preparing a wear-resistant coating, comprising the following steps: Step 1: Add 7.4g of 1,6-dibromohexane and 4.2g of potassium carbonate to 125g of acetonitrile, then add 24g of a 15wt% p-hydroxybenzaldehyde / acetonitrile mixture dropwise at a rate of 1mL / min. Heat to 70℃ and reflux for 6h. After the reaction is complete, evaporate the solvent and filter to obtain intermediate product A. Add 8.1g of p-phenylenediamine to 300g of acetonitrile, then add 21.4g of intermediate product A dropwise at a rate of 1mL / min. React the reaction mixture at 70℃ for 12h. After the reaction is complete, filter, wash the obtained solid product four times with acetonitrile, and dry under vacuum at 65°C to obtain intermediate product B. Step 2: Add 4.5g of surface-modified silicon carbide / silica composite material to 125g of N,N-dimethylformamide, sonicate for 30min, then add 2.8g of intermediate product B, react at 80℃ for 25h. After the reaction, centrifuge, wash the obtained solid product 4 times with N,N-dimethylformamide, and vacuum dry at 50℃ to obtain organic-inorganic hybrid filler; add 4.5g of organic-inorganic hybrid filler to 125g of N,N-dimethylformamide, then add 2.9g of N-methyldiethanolamine, stir and react at 60℃ for 6h. After the reaction, centrifuge, wash the obtained solid product 4 times with N,N-dimethylformamide, and vacuum dry at 50℃ to obtain modified organic-inorganic hybrid filler; Step 3: Add 30g of polytetrahydrofuran and 10.1g of 2,2-dimethylolpropionic acid to 125g of N,N-dimethylacetamide, stir for 35 min, then add 19.9g of the hydrazide compound prepared in Example 1, stir, then add 31.2g of toluene diisocyanate and 0.2g of dibutyltin dilaurate, heat to 70℃, react for 2.5 h, then add 14.9g of trimethylolpropane, react at 70℃ for 2 h, then add 5.7g of pentaerythritol triacrylate and 2.5g of hydroxyethyl methacrylate, react at 65℃ for 2 h, then add 6.9g of modified organic-inorganic hybrid filler, react at 65℃ for 1.5 h, then add 7.6g of trimethylolpropane. Ethylamine was reacted at 65°C for 12 min, and N,N-dimethylacetamide was removed by rotary evaporation. 265 g of deionized water was added to the reaction mixture, and emulsification was carried out at 25°C for 1 h. Then, 10.5 g of pentaerythritol tetrakis(3-mercaptopropionic acid) was added, and the mixture was reacted at 25°C for 1.5 h to obtain an aqueous polyurethane acrylate emulsion. By weight, 90 parts of the aqueous polyurethane acrylate emulsion, 1 part of diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, 9 parts of ethoxylated trimethylolpropane triacrylate, and 3 parts of titanium dioxide were mixed evenly to obtain a wear-resistant coating.

[0025] Comparative Example 2 This comparative example discloses a method for preparing a wear-resistant coating, comprising the following steps: Step 1: Add 7.4g of 1,6-dibromohexane and 4.2g of potassium carbonate to 125g of acetonitrile, then add 24g of a 15wt% p-hydroxybenzaldehyde / acetonitrile mixture dropwise at a rate of 1mL / min. Heat to 70℃ and reflux for 6h. After the reaction is complete, evaporate the solvent and filter to obtain intermediate product A. Add 8.1g of p-phenylenediamine to 300g of acetonitrile, then add 21.4g of intermediate product A dropwise at a rate of 1mL / min. React the reaction mixture at 70℃ for 12h. After the reaction is complete, filter, wash the obtained solid product four times with acetonitrile, and dry under vacuum at 65°C to obtain intermediate product B. Step 2: Add 4.5g of surface-modified silicon carbide / silica composite material to 125g of N,N-dimethylformamide, sonicate for 30min, then add 2.8g of intermediate product B, react at 80℃ for 25h. After the reaction, centrifuge, wash the obtained solid product 4 times with N,N-dimethylformamide, and vacuum dry at 50℃ to obtain organic-inorganic hybrid filler; add 4.5g of organic-inorganic hybrid filler to 125g of N,N-dimethylformamide, then add 2.9g of N-methyldiethanolamine, stir and react at 60℃ for 6h. After the reaction, centrifuge, wash the obtained solid product 4 times with N,N-dimethylformamide, and vacuum dry at 50℃ to obtain modified organic-inorganic hybrid filler; Step 3: Add 30g of polytetrahydrofuran and 10.1g of 2,2-dimethylolpropionic acid to 125g of N,N-dimethylacetamide, stir for 35 minutes, then add 31.2g of toluene diisocyanate and 0.2g of dibutyltin dilaurate, heat to 70℃, and react for 2.5 hours. Then add 14.9g of trimethylolpropane and react at 70℃ for 2 hours. Next, add 5.7g of pentaerythritol triacrylate and 2.5g of hydroxyethyl methacrylate, and react at 65℃ for 2 hours. Then add 6.9g of modified organic-inorganic hybrid filler and react at 65℃ for 1.5 hours. Finally, add 7.6g of triethylamine and react at 65℃ for 12 hours. After removing N,N-dimethylacetamide by rotary evaporation, 265g of deionized water was added to the reaction mixture, and emulsification was carried out at 25°C for 1 hour. Then, 10.5g of pentaerythritol tetrakis(3-mercaptopropionic acid) was added, and the reaction was carried out at 25°C for 1.5 hours to obtain an aqueous polyurethane acrylate emulsion. By weight, 90 parts of the aqueous polyurethane acrylate emulsion, 1 part of diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, 9 parts of ethoxylated trimethylolpropane triacrylate, and 3 parts of titanium dioxide were mixed evenly to obtain a wear-resistant coating.

[0026] Comparative Example 3 This comparative example discloses a method for preparing a wear-resistant coating, comprising the following steps: Step 1: Add 7.4g of 1,6-dibromohexane and 4.2g of potassium carbonate to 125g of acetonitrile, then add 24g of a 15wt% p-hydroxybenzaldehyde / acetonitrile mixture dropwise at a rate of 1mL / min. Heat to 70℃ and reflux for 6h. After the reaction is complete, evaporate the solvent and filter to obtain intermediate product A. Add 8.1g of p-phenylenediamine to 300g of acetonitrile, then add 21.4g of intermediate product A dropwise at a rate of 1mL / min. React the reaction mixture at 70℃ for 12h. After the reaction is complete, filter, wash the obtained solid product four times with acetonitrile, and dry under vacuum at 65°C to obtain intermediate product B. Step 2: Add 4.5g of surface-modified silicon carbide / silica composite material to 125g of N,N-dimethylformamide, sonicate for 30min, then add 2.8g of intermediate product B, react at 80℃ for 25h. After the reaction, centrifuge, wash the obtained solid product 4 times with N,N-dimethylformamide, and vacuum dry at 50℃ to obtain organic-inorganic hybrid filler; add 4.5g of organic-inorganic hybrid filler to 125g of N,N-dimethylformamide, then add 2.9g of N-methyldiethanolamine, stir and react at 60℃ for 6h. After the reaction, centrifuge, wash the obtained solid product 4 times with N,N-dimethylformamide, and vacuum dry at 50℃ to obtain modified organic-inorganic hybrid filler; Step 3: Add 30g of polytetrahydrofuran and 10.1g of 2,2-dimethylolpropionic acid to 125g of N,N-dimethylacetamide and stir for 35 minutes. Then add 19.9g of multifunctional modifier and stir. Next, add 31.2g of toluene diisocyanate and 0.2g of dibutyltin dilaurate, heat to 70℃, and react for 2.5 hours. Then add 14.9g of trimethylolpropane and react at 70℃ for 2 hours. Then add 5.7g of pentaerythritol triacrylate and 2.5g of hydroxyethyl methacrylate and react at 65℃ for 2 hours. Finally, add 7.6g of triethylamine and react at 65℃ for 12 minutes. Rotary evaporate the mixture. After removing N,N-dimethylacetamide, 265g of deionized water was added to the reaction mixture, and emulsification was carried out at 25°C for 1 hour. Then, 10.5g of pentaerythritol tetrakis(3-mercaptopropionic acid) was added, and the mixture was reacted at 25°C for 1.5 hours to obtain an aqueous polyurethane acrylate emulsion. By weight, 90 parts of the aqueous polyurethane acrylate emulsion, 1 part of diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, 9 parts of ethoxylated trimethylolpropane triacrylate, and 3 parts of titanium dioxide were mixed evenly to obtain a wear-resistant coating.

[0027] Comparative Example 4 This embodiment discloses a method for preparing a wear-resistant coating, including the following steps: Step 1: Add 7.4g of 1,6-dibromohexane and 4.2g of potassium carbonate to 125g of acetonitrile, then add 24g of a 15wt% p-hydroxybenzaldehyde / acetonitrile mixture dropwise at a rate of 1mL / min. Heat to 70℃ and reflux for 6h. After the reaction is complete, evaporate the solvent and filter to obtain intermediate product A. Add 8.1g of p-phenylenediamine to 300g of acetonitrile, then add 21.4g of intermediate product A dropwise at a rate of 1mL / min. React the reaction mixture at 70℃ for 12h. After the reaction is complete, filter, wash the obtained solid product four times with acetonitrile, and dry under vacuum at 65°C to obtain intermediate product B. Step 2: Add 4.5g of surface-modified silicon carbide / silica composite material to 125g of N,N-dimethylformamide, sonicate for 30min, then add 2.8g of intermediate product B, react at 80℃ for 25h. After the reaction, centrifuge, wash the obtained solid product 4 times with N,N-dimethylformamide, and vacuum dry at 50℃ to obtain organic-inorganic hybrid filler; add 4.5g of organic-inorganic hybrid filler to 125g of N,N-dimethylformamide, then add 2.9g of N-methyldiethanolamine, stir and react at 60℃ for 6h. After the reaction, centrifuge, wash the obtained solid product 4 times with N,N-dimethylformamide, and vacuum dry at 50℃ to obtain modified organic-inorganic hybrid filler; Step 3: Add 30g of polytetrahydrofuran and 10.1g of 2,2-dimethylolpropionic acid to 125g of N,N-dimethylacetamide, stir for 35 minutes, then add 19.9g of multifunctional modifier, stir, then add 31.2g of toluene diisocyanate and 0.2g of dibutyltin dilaurate, heat to 70℃, react for 2.5 hours, then add 14.9g of trimethylolpropane, react at 70℃ for 2 hours, then add 5.7g of pentaerythritol triacrylate and 2.5g of hydroxyethyl methacrylate, react at 65℃ for 2 hours, then add 6.9g of modified organic-inorganic hybrid filler, and react at 65℃. After 1.5 hours, 7.6 g of triethylamine was added, and the mixture was reacted at 65°C for 12 minutes. N,N-dimethylacetamide was removed by rotary evaporation. 265 g of deionized water was added to the reaction mixture, and the mixture was emulsified at 25°C for 1 hour to obtain an aqueous polyurethane acrylate emulsion. By weight, 90 parts of the aqueous polyurethane acrylate emulsion, 1 part of diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, 9 parts of ethoxylated trimethylolpropane triacrylate, and 3 parts of titanium dioxide were mixed evenly to obtain a wear-resistant coating.

[0028] In the above examples and comparative examples, silicon carbide (average particle size: 10 μm) was from Qinghe County Kete New Material Technology Co., Ltd.; polytetrahydrofuran, with an average molecular weight of 2000, was from Shandong Jining Baichuan Chemical Co., Ltd.

[0029] Experimental Example Using the wear-resistant coatings prepared in Examples 3-5 and Comparative Examples 1-4, electroplated aluminum film samples were prepared. The method was as follows: PET film was selected, and a water-based wax with a solid content of 20 wt% was coated on the film and dried to form a release layer; then, the wear-resistant coating was coated onto the release layer at a coating amount of 1.4 g / m². 2 The film was cured under a 500W UV lamp for 30 seconds to form a color layer; then aluminum plating was performed to form an aluminum layer with an OD value of 2.0; finally, adhesive was applied and dried to form an adhesive layer, thus obtaining the electroplated aluminum film. Performance tests were conducted on each group of electroplated aluminum films.

[0030] I. Abrasion Resistance Test: The electroplated aluminum foil is hot-stamped onto the surface of the substrate at 125℃ to form a hot-stamped layer. The film is then peeled off. The substrate is packaging cardboard. Then, according to "4.5.2 Abrasion Resistance of Hot-Stamped Layer" in GB 10456-1989 "Electroplated Aluminum Hot Stamping Foil", the abrasion resistance As is measured. The higher the abrasion resistance As, the better the abrasion resistance.

[0031] II. Heat Resistance Test: The prepared electroplated aluminum film is hot-stamped onto the surface of the substrate at 150℃ to form a hot-stamping layer. The film is then peeled off. The substrate is packaging cardboard, and the hot-stamped pattern is a square pattern with an area of ​​50mm×50mm. After hot stamping, the gloss of the square pattern is observed. The brighter the gloss, the better the heat resistance.

[0032] III. Antibacterial Performance Test: Staphylococcus aureus (ATCC 6538) was selected and inoculated into LB liquid medium. It was cultured at 37℃ to the logarithmic growth phase (OD600≈0.5). 100 μL of bacterial suspension (concentration 1×106 CFU / mL) was evenly spread on the sample surface, covered with sterile polyethylene film, and incubated at 37℃ and 90%RH for 24 hours. The bacterial cells were washed off with PBS buffer, serially diluted, and spread on agar plates. The coated sample was placed in a constant temperature and humidity chamber (85℃, 85%RH). After 50 hours, the sample was taken and the antibacterial rate was tested according to ISO 22196.

[0033] The test results are shown in Table 1:

[0034] As shown in Table 1, the wear-resistant coatings prepared in Examples 3-5 of this invention possess heat resistance, wear resistance, and antibacterial properties. A comparison between Comparative Examples 1-2 and Example 5 reveals that introducing a multifunctional modifier into the polyurethane acrylate system, with the presence of phosphate ester compounds and hydrazide compounds, introduces aromatic benzene ring structures, phosphate ester groups, dynamic hydrazone bonds, and phenolic hydroxyl groups, thereby improving the overall performance of the waterborne polyurethane acrylate coating. A comparison between Comparative Example 3 and Example 5 shows that the modified organic-inorganic hybrid filler can also form an organic-inorganic interpenetrating network with the polyurethane acrylate system, endowing the waterborne polyurethane acrylate coating with excellent mechanical properties, wear resistance, heat resistance, and antibacterial properties. A comparison between Comparative Example 4 and Example 5 shows that the introduction of pentaerythritol tetrakis(3-mercaptopropionic acid) ester as a crosslinking agent in the polyurethane acrylate system further improves the wear resistance and heat resistance of the polyurethane acrylate coating.

[0035] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a wear-resistant coating, characterized in that, Includes the following steps: Step 1: 1,6-Dibromohexane reacts with p-hydroxybenzaldehyde to give intermediate A; intermediate A reacts with p-phenylenediamine to give intermediate B. Step 2: Modify the surface-modified silicon carbide / silica composite material with intermediate product B to obtain an organic-inorganic hybrid filler; treat the organic-inorganic hybrid filler with N-methyldiethanolamine to obtain a modified organic-inorganic hybrid filler. Step 3: Introduce the multifunctional modifier, modified organic-inorganic hybrid filler, and pentaerythritol tetrakis(3-mercaptopropionic acid) into the polyurethane acrylate structure to prepare an aqueous polyurethane acrylate emulsion; mix the aqueous polyurethane acrylate emulsion, diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, ethoxylated trimethylolpropane triacrylate, and titanium dioxide in a certain proportion to obtain a wear-resistant coating.

2. The method for preparing the wear-resistant coating according to claim 1, characterized in that, In step one, the preparation method of intermediate product B specifically includes: adding 1,6-dibromohexane and potassium carbonate to acetonitrile, then adding 15wt% p-hydroxybenzaldehyde / acetonitrile mixture, heating to 67-73℃, refluxing for 5-7h, purifying to obtain intermediate product A; wherein the mass ratio of 1,6-dibromohexane, potassium carbonate, acetonitrile, and p-hydroxybenzaldehyde / acetonitrile mixture is (4.9-9.8):(2.8-5.6):(100-150):(16-32); adding p-phenylenediamine to acetonitrile, then adding intermediate product A, reacting the reaction mixture at 65-75℃ for 10-14h, purifying to obtain intermediate product B; wherein the mass ratio of p-phenylenediamine, acetonitrile, and intermediate product A is (5.4-10.8):(250-350):(14.3-28.5).

3. The method for preparing the wear-resistant coating according to claim 1, characterized in that, In step two, the preparation method of the modified organic-inorganic hybrid filler specifically includes: adding the surface-modified silicon carbide / silica composite material to N,N-dimethylformamide, sonicating, then adding intermediate product B, reacting at 75-85℃ for 20-30h, purifying, and obtaining the organic-inorganic hybrid filler; wherein, the mass ratio of the surface-modified silicon carbide / silica composite material, N,N-dimethylformamide, and intermediate product B is (4-5):(100-150):(1.9-3.8); mixing the organic-inorganic hybrid filler, N,N-dimethylformamide, and N-methyldiethanolamine at a mass ratio of (4-5):(100-150):(2.2-3.6), stirring and reacting at 58-62℃ for 5-7h, purifying, and obtaining the modified organic-inorganic hybrid filler.

4. The method for preparing the wear-resistant coating according to claim 3, characterized in that, The surface-modified silicon carbide / silica composite material is prepared by the following method: Silicon carbide is heated from room temperature to 1000-1200℃ at a rate of 5℃ / min in an air atmosphere, held for 1.5-2.5h, and cooled to room temperature to obtain the silicon carbide / silica composite material; distilled water is mixed with silane coupling agent KH-560, stirred, and then ethanol and the silicon carbide / silica composite material are added. The pH of the mixture is adjusted to 4-5 with acetic acid, heated to 68-72℃, stirred for 5-7h, purified, and ground to obtain the surface-modified silicon carbide / silica composite material; wherein the mass ratio of distilled water, silane coupling agent KH-560, ethanol, and silicon carbide / silica composite material is (15-30):(5-10):(135-270):(4-5).

5. The method for preparing the wear-resistant coating according to claim 1, characterized in that, In step three, the preparation method of the waterborne polyurethane acrylate emulsion specifically includes: adding polytetrahydrofuran and 2,2-dimethylolpropionic acid to N,N-dimethylacetamide, stirring, then adding a multifunctional modifier, stirring, then adding toluene diisocyanate and dibutyltin dilaurate, heating to 68-72℃, reacting for 2-3 hours, then adding trimethylolpropane, reacting at 68-72℃ for 1.5-2.5 hours, and then adding pentaerythritol triacrylate and methyl... Hydroxyethyl acrylate is reacted at 62-68℃ for 1.5-2.5 h, then modified organic-inorganic hybrid filler is added and reacted at 62-68℃ for 1-2 h, then triethylamine is added and reacted at 62-68℃ for 10-15 min, rotary evaporated, deionized water is added to the reaction mixture, and emulsification is carried out at 23-27℃ for 1 h, then pentaerythritol tetrakis(3-mercaptopropionic acid) is added and reacted at 23-27℃ for 1-2 h to obtain an aqueous polyurethane acrylate emulsion.

6. The method for preparing the wear-resistant coating according to claim 5, characterized in that, The mass ratio of the multifunctional modifier, N,N-dimethylacetamide, polytetrahydrofuran, 2,2-dimethylolpropionic acid, toluene diisocyanate, dibutyltin dilaurate, trimethylolpropane, pentaerythritol triacrylate, hydroxyethyl methacrylate, modified organic-inorganic hybrid filler, triethylamine, deionized water, and pentaerythritol tetrakis(3-mercaptopropionic acid) ester is (13.3-26.6): (100-150): (20-40): (6.7-13.4): (20.8-41.5): (0.1-0.2): (13.2-16.6): (3.8-7.5): (1.7-3.3): (4.3-9.5): (5.1-10.1): (180-350): (6-15).

7. The method for preparing the wear-resistant coating according to claim 1, characterized in that, In step three, the mass ratio of waterborne polyurethane acrylate emulsion, diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, ethoxylated trimethylolpropane triacrylate, and titanium dioxide in the wear-resistant coating is (80-100):(0.8-1.2):(8-10):(1.5-4.5).

8. The method for preparing the wear-resistant coating according to claim 1, characterized in that, The multifunctional modifier in step three is prepared by the following methods: Step S1: Mix hydroxyethyl methacrylate and hydroquinone monomethyl ether, stir at 0°C, then add phosphorus pentoxide, heat to 48-52°C, react for 5.5-6.5 h, then add hydroxyethyl methacrylate again, heat to 68-72°C, react for 40-80 min, purify to obtain the phosphate ester compound; wherein the mass ratio of hydroxyethyl methacrylate, hydroquinone monomethyl ether, and phosphorus pentoxide is (13.7-27.4):(1.5-3):( 7.1-14.2); 3-mercaptopropionic acid is added to ethanol and heated to 60-70℃. Then, a phosphate ester compound and a 0.5wt% azobisisobutyronitrile / ethanol mixture are added. The mixture is stirred and reacted for 3-5 hours. After purification, the modified phosphate ester compound is obtained. The mass ratio of 3-mercaptopropionic acid, ethanol, phosphate ester compound, and azobisisobutyronitrile / ethanol mixture is (2.1-4.2):(120-150):(3.2-6.4):(15-20). Step S2: Mix 13.1wt% succinic acid dihydrazide aqueous solution and 20wt% 4-amino-2-hydroxybenzaldehyde / ethanol mixture at a mass ratio of (28.7-57.5):(35-70), stir and react at 65-75℃ for 2.5-3.5h, and purify to obtain the hydrazide compound; mix the modified phosphate ester compound, N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride, N-hydroxysuccinimide, N,N-dimethylformamide, and hydrazide compound at a mass ratio of (5.3-10.6):(4.8-9.6):(2.8-5.6):(200-300):(7.7-15.4), stir and react at 60-80℃ for 6-10h, and purify to obtain the multifunctional modifier.

9. An abrasion-resistant coating prepared by the method for preparing abrasion-resistant coatings as described in any one of claims 1-8.

10. The application of the wear-resistant coating according to claim 9 on an electroplated aluminum color layer.

Citation Information

Patent Citations

  • Wearproof color layer coating, formed wearproof color layer, wearproof alumite and preparation method thereof

    CN107629603A

  • Antibacterial UV curing alumite color layer coating and preparation method thereof

    CN119955362A

  • Room temperature self-crosslinking type PUA-SiO2 hybrid emulsion and preparation method thereof

    CN107201129A

  • Metal anticorrosive emulsion and preparation method thereof

    CN111187387A

  • Anti-corrosion functional silicon dioxide modified epoxy composite coating and preparation method thereof

    CN114015322A